THE INFLUENECE OF THE SMALL TALK STRATEGY ON PERSONAL BRANDING USED BY “JIMMY FALLON” IN YOUTUBE - Amaliya, Amaliya; Mahmud, Murni; Burhamzah, Muftihaturrahmah (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
Small talk is light-hearted conversation that is usually done to cure boredom or to start a conversation with someone new. Usually, the topics discussed in small talk are not very deep or serious, such as the weather, daily activities, or hobbies. The main purpose of small talk is to build intimacy or rapport with others. This research aims to find out the effect of small talk in introducing personal branding and how to make small talk with the public to introduce personal branding. This research uses descriptive qualitative methods in analyzing data. There are two sources used, namely Primary and secondary. According to Peter Montoya in Haroen (2014) there are 8 personal branding concepts that must exist in a public figure, including The Law of Visibility, The Law of Specialization, The Law of Unity, The Law of Leadership, The Law of Persistence, The Law of Personality, The Law of GoodWill, and The Law of Distinctiveness. Based on this research, we found 31 extracts included in 8 Specialization, 1 Leadership, 7 Personality, 4 Distinctiveness, 4 Visibility, 2 Unity, 4 Persistence, and 1 Goodwill. Keywords : Small Talk, Personal Branding, Jimmy Fallon,